Robust Open Circuit Fault Tolerance for Five-Level HANPC Inverters Using an Improved SV-PWM Modulation - Halabi, Laith M.; Lee, Kyo Beum (2022 IEEE Energy Conversion Congress and Exposition, ECCE 2022, 2022)
In power conversion systems, open circuit faults could occur at any stage of the system operation. Mainly the faults occurring at the switching level have higher impact on the system. In this regard, this paper proposed a robust open circuit fault tolerance method that is able to recover the normal operation over the different cases of the open circuit faults in fife-level hybrid active natural point clamped converters (HANPC). The proposed method operates by modifying the original voltage references in order to eliminates the fault effects besides generating new switching sequences for all cases of the open circuit faults. Meanwhile, the proposed method does not require the insertion of any extra hardware or changes to the basic topology of the inverter. Correspondingly, the proposed method is explained and clarified in detail and result in reobtaining normal operation for all faulty cases safely and adequately. In addition to balancing the DC link voltage without any special requirements to withstand under high voltage levels. The proposed method is verified by simulation results.
Keywords: High impact; Hybrid active natural point clamped converter; Multilevel inverter; Multilevels; Normal operations; Open-circuit fault; Power conversion systems; SV-PWM modulation; Switching levels; Systems operation; fault tolerance; HANPC; multilevel inverters; SV-PWM modulation